Impact of Lithium Composition on Structural, Electronic and Optical Properties of Lithium Cobaltite Prepared by Solid-state Reaction - Khatun, F.; Gafur, M. A.; Ali, M. S.; Islam, M. S.; Sarker, M. A. R. (Journal of Scientific Research, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> The lithium-cobalt oxide LixCoO2 is a promising candidate as highly active cathode material of lithium ion rechargeable batteries. The crystalline-layered lithium cobaltite has attracted increased attention due to recent discoveries of some extraordinary properties such as unconventional transport and magnetic properties. Due to layered crystal structure, Li contents (x) in LixCoO2 might play an important role on its interesting properties. LiCoO2 crystalline cathode material was prepared by using solid-state reaction synthesis, and then LixCoO2 (x<1) has been synthesized by deintercalation of produced single-phase powders. Structure and morphology of the synthesized powders were investigated by X-ray diffraction (XRD), Infrared spectroscopy, Impedance analyzer etc. The influence of lithium composition (x) on structural, electronic and optical properties of lithium cobaltite was studied. Temperature dependent electrical resistivity was measured using four-probe technique. While LixCoO2 with x = 0.9 is a semiconductor, the highly Li-deficient phase (0.75 ? x ? 0.5) exhibits metallic conductivity. The ionic conductivity of LixCoO2 (x = 0.5 1.15) was measured using impedance spectroscopy and maximum conductivity of Li0.5CoO2 was found to be 6.5×10-6 S/cm at 273 K. The properties that are important for applications, such as ionic conductivity, charge capacity, and optical absorption are observed to increase with Li deficiency. Keywords: Calcination; Characterization; Inorganic compounds; Solid-State reaction; X-ray diffraction. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17900 J. Sci. Res. 6 (2), 217-231 (2014)